Existing Challenges in Clinical Governance Establishment Evaluation Based on National Assessors\' Aspect (A Qualitative Study) - Hamid Ravaghi; Sima Rafiei; Maryam Mohseni; Peigham Heidarpour; Mohammad Arab (Tehran University of Medical Sciences, 2016)
Background: Clinical Governance (CG) is a framework which obligates heath care system to responsiveness regarding maintaining and improving health care serviceschr('39') quality. Purpose of this study was to exists challenges in Clinical Governance establishment evaluation based on national assessorschr('39') aspect. Materials and Methods: This qualitative study was conducted with national assessorschr('39') participation of Clinical Governance plan in 2014.Data collection was carried out using face to face interviews with assessors  and analyzed  based on content analysis. Results: Three main themes were categorized including problems related to clinical governance standards, Existing challenges in assessment process and recommendations to improve quality assessment process. From the assessorschr('39') aspects, the main existing challenges were lack of knowledge and adequate skills in some assessors towards CG, lack of sufficient accordance among assessors team, resistance of some universities and health care systems, lack of existing comprehensive guidelines with the purpose of responsiveness in related ambiguity in assessment and direction process among assessors. Conclusion: Reinforcement of quality improvement culture in hospitals and increasing susceptibility in plan continuation, correct assessors election and ensuring about knowledge in responsibilities, updating assessorschr('39') training and putting to use equal indices in improving clinical governance assessment can be a considerable assist to improve assessment process and resolve related problems.